Helical Nanostructures: Broadband Enhanced Chirality with Tunable Response in Hybrid Plasmonic Helical Metamaterials (Adv. Funct. Mater. 20/2021). (17th May 2021) - Kilic, Ufuk; Hilfiker, Matthew; Ruder, Alexander; Feder, Rene; Schubert, Eva; Schubert, Mathias; Argyropoulos, Christos
Abstract : Chiral light‐matter interactions have an extremely weak nature, are difficult to be controlled and enhanced, and cannot be made tunable or broadband. In article number 2010329, Ufuk Kilic, Christos Argyropoulos, and co‐workers tackle these important problems by experimentally demonstrating and theoretically verifying spectrally tunable, extremely large, and broadband circular dichroism from new hybrid dielectric and plasmonic nanohelical metamaterial configurations operating at the technologically important visible to ultra‐violet spectrum.